Kemampuan Membaca Pemahaman Dengan Penerapan Strategi Know, Want, Learning (K-W-L) Di Kabupaten Sidrap - Lapi, Misnawati; Madjid, Syahria; Muhammadiah, Mas'ud (Jounal of Primary Education, 2023)
Tujuan penelitian adalah untuk mengetahui penerapan strategi K-W-L (Know-Want-Learn) dalam meningkatkan hasil belajar membaca pemahaman siswa,  peningkatkan hasil belajar membaca pemahaman, dan penerapan strategi K-W-L (Know-Want-Learn) dalam meningkatkan hasil belajar membaca pemahaman siswa kelas V UPT SD Negeri 5 Lawawoi. Jenis penelitian ini adalah Penelitian Tindakan Kelas (Classroom Action Research). Sampel berjumlah 18 siswa, terdiri atas 8 siswa laki-laki dan 10 siswi perempuan. Metode pengumpulan data yang digunakan yaitu tes dan observasi, sedangkan teknik analisis data yang digunakan yaitu menganalisis hasil observasi dan analisis hasil tes kemampuan membaca pemahaman.Berdasarkan hasil analisis, maka diperoleh hasil tes keterampilan membaca pemahaman siklus I dengan nilai rata-rata 57,02 dan kriteria ketuntasan belajarnya mencapai 55%,  begitu pula dengan tes hasil belajar dengan nilai rata-rata 52,33 dan kriteria ketuntasan belajarnya mencapai 33%, selanjutnya mengalami peningkatan pada siklus II yakni nilai rata-rata setiap individu 86,27 dengan kriteria ketuntasan belajarnya mencapai 89% untuk kemampuan membaca pemahaman dan untuk hasil belajar mengalami peningkatan nilai ratar-ata yakni 89,41 dengan kriteria ketuntasan sebesar 94%.. The research objectives were to find out: (1) the application of the K-W-L (Know-Want-Learn) strategy in improving students' reading comprehension learning outcomes, (2) the improvement of reading comprehension learning outcomes, and (3) the application of the K-W-L (Know-Want-Learn) strategy in improving students' reading comprehension learning outcomes in fifth grade UPT SD Negeri 5 Lawawoi. This type of research is Classroom Action Research (PTK). The sample amounted to 18 students, consisting of 8 male students and 10 female students. The data collection methods used are tests and observations, while the data analysis techniques used are analyzing the results of observations and analyzing the results of reading comprehension ability tests. Based on the results of the analysis, the results of the reading comprehension skills test in cycle I were obtained with an average value of 57.02 and the criteria for learning completeness reached 55%, as well as the learning outcomes test with an average value of 52.33 and the criteria for learning completeness reached 33%, then experienced an increase in cycle II, namely the average value of each individual 86.27 with the criteria for learning completeness reaching 89% for reading comprehension skills and for learning outcomes increased the average value of 89.41 with the criteria for completeness of 94%. Based on these results, it can be concluded that the application of the K-W-L (Know-Want-Learn) strategy in improving student reading comprehension learning outcomes in fifth grade students of UPT SD Negeri 5 Lawawoi.